2022
DOI: 10.1002/tox.23725
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3 downregulates IL4i1 aggravating lipopolysaccharide‐induced acute lung injury via H3K27 and H3K4 demethylation

Abstract: The pro‐inflammation M1 to anti‐inflammation M2 macrophage ratio contribute to the severity of lipopolysaccharide (LPS)‐induced acute lung injury (ALI). JMJD3 aggravates the inflammatory reaction through affecting epigenetic modification and macrophage's phenotype to deteriorate ALI. To explore the mechanism underlying the upregulation of the macrophage M1/M2 ratio through JMJD3, we developed an ALI mouse model using intratracheal LPS, LPS‐stimulated RAW 264.7 cells, and inhibited JMJD3 using GSK‐J4. H3K27me3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…IL4I1 has been associated mainly with the immunoregulation and oncogenic properties of multiple tumors, which could be attributed to its ability to convert amino acids, generate H 2 O 2 , or exhibit an enzyme-independent function (42, 43). Specifically, IL4I1 has been demonstrated to oxidize phenylalanine into phenylpyruvic acid and H 2 O 2 , as well as to convert tyrosine and Trp into hydroxyphenylpyruvic (HPP) acid and I3P, respectively (44,45). Previous studies have shown that IL4I1 could augment growth vitality of cancer cells and diminish the motility of CD8+ T cells through the I3P-aryl hydrocarbon receptor (AHR) axis (17).…”
Section: Discussionmentioning
confidence: 99%
“…IL4I1 has been associated mainly with the immunoregulation and oncogenic properties of multiple tumors, which could be attributed to its ability to convert amino acids, generate H 2 O 2 , or exhibit an enzyme-independent function (42, 43). Specifically, IL4I1 has been demonstrated to oxidize phenylalanine into phenylpyruvic acid and H 2 O 2 , as well as to convert tyrosine and Trp into hydroxyphenylpyruvic (HPP) acid and I3P, respectively (44,45). Previous studies have shown that IL4I1 could augment growth vitality of cancer cells and diminish the motility of CD8+ T cells through the I3P-aryl hydrocarbon receptor (AHR) axis (17).…”
Section: Discussionmentioning
confidence: 99%